THE INTER-AMERICAN HUMAN RIGHTS SYSTEM FIFTY YEARS LATER: TIME FOR CHANGES - Dulitzky, Ariel (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2011)
This article analyzes the latest reforms of rules and regulations of the Inter-American Commission on Human Rights (IACHR) and the Inter-American Court of Human Rights and the overall functioning of the Inter-American human rights system. Particularly the article focuses on the strengths and weaknesses of the judicialization of the Inter-American amparo. The paper identifies the measures necessary to allow the Inter-American system to play a more prominent role in the promotion and protection of human rights. Specific measures include mainstreaming the work of the OAS around human rights issues, including in the Inter-American Democratic Charter a stronger link between democracy and the protection of human rights, and balancing the work on individual complaints with other tools available to the IACHR. It proposes a fundamental change in the IACHR’s profile through the modification of its participation in the individual petition system. The Commission should only act as an organ of admissibility and facilitator of friendly solutions, and the Court as a tribunal that carries out findings of fact and makes legal determinations on the merits of complaints. The IACHR needs to concentrate more heavily on political and promotional activities that complement its limited participation in the processing of individual cases.